An obstructed spigelian hernia with ipsilateral cryptorchidism: A rare case scenario of an obstructed spigelian hernia with ipsilateral cryptorchidism (Indian Journal of Case Reports, 2024)
A spigelian hernia is the type of ventral hernia that appears in the abdomen’s lower quadrant between an area of dense fibrous tissue and abdominal wall muscles, forming a spigelian aponeurosis. Undescended testicle” is the term used when one or both of the testicles fail to descend into the scrotum. Here, we report the case of a right lower quadrant spigelian hernia with ipsilateral undescended testes that may be a part of the new spigelian-cryptoorchidism syndrome in a 27-year-old male. An exploratory laparotomy was performed via the right paramedian incision. The right-sided orchidectomy was also done. The resected bowel and testes were sent for histopathological examination. The patient was discharged and is doing well on follow-up visits.